Leadership According to the Buddhist Concepts (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This academic article aims to study about leadership according to the Buddhist concepts which can be said thatBuddhist leadership is a process of influence in which leaders on individuals or groups lead to the achievement of goals that allare willing and mutually satisfied by interacting, conveying ideas into the continued action of A process that relates andinfluences between a leader, followers, and a situation or a task using Buddhist concepts as the main leading.(SamritKangpeng, 2019). So a really great leader is who can put truth, righteousness as a reference that allows people to joinforces in the creation of life and society without the need for greed or anger as a stimulus. (Phraphromkhunaphorn,P.A.Payutto, 2005). Leadership individuals must be willing to tolerate problems arising from the performance of their assignedduties to the best of their ability leading to the promotion of better management and sustainability which must consist of virtuesin self-management, namely 1) Alms is a sacrifice to share in a way of giving relief 2) The precepts are the focus and care ofone's body and speech, not to hurt oneself, others and society. 3) Nekkhamma is to refrain from sins and various kinds of evil.4) Wisdom is knowledge 5) Effort is persistence 6) Endurance is patience. Patience is the quality of being a leader inBuddhism.